Application of reused material concept in the rusunawa planning (ARTEKS : Jurnal Teknik Arsitektur, 2021)
The need for adequate and affordable housing drives the government to implement the rusunawa (low-cost housing) development program in various regions. Futhermore, the government promotes utilization of different replacement materials to optimize the cost and duration of rusunawa development, including reused shipping container. This research discusses the feasibility study of reused shipping containers as substitute material in the design planning of the Rusunawa prototype unit construction. It is a qualitative research that uses case study and statistical data-sets through literature review, precedent study analysis and field surveys. The results provided the standard guideline for designing Rusunawa units made from reused shipping containers and prototype typology units based on the occupant’s type.
Keywords: Slums; Reused shipping containers; Rental flats